A Simulated Case of Acute Salicylate Toxicity From an Intentional Overdose - Richard L. Lammers; Maria L. Sheakley; Sean Hendren (Association of American Medical Colleges, 2018)
Introduction Salicylate poisoning is a serious toxicologic problem with a complex pathophysiology that requires prompt diagnosis and action for a favorable outcome. A simulated experience in the evaluation and management of an aspirin-overdose patient allows learners to construct a differential diagnosis from an array of symptoms and signs, analyze a mixed acid-base disturbance, and explore the multistep management of this disorder. Methods This simulation exercise was designed for second-year medical students. At the start of the session, teams received a 10-minute introduction to the activity. Upon entering a room in a simulated Emergency Department, teams had 15 minutes to complete a focused history and physical exam of the patient, interpret arterial blood gas and basic metabolic panel data, and administer treatment based on key findings and a presumptive diagnosis. The scenario was followed by a 90-minute facilitated debriefing session. An alternative 45-minute debriefing guideline is also included. Results Students voluntarily completed a 13-question, 5-point Likert-scale survey about the educational exercise immediately following the session. They evaluated the preparatory materials and briefing, the simulation scenario, the usefulness of the debriefing, and their confidence in their understanding of salicylate poisoning following the session. Students reported a favorable response to the overall experience and the debriefing, as well as an increase in confidence following the session. Discussion This simulation exercise was successful in exposing students to the clinical presentation of salicylate toxicity and giving them the opportunity to apply and synthesize basic science knowledge during the scenario.